NFATC1 activation by DNA hypomethylation in chronic lymphocytic leukemia correlates with clinical staging and can be inhibited by ibrutinib. Issue 2 (9th October 2017) - Wolf, Christine; Garding, Angela; Filarsky, Katharina; Bahlo, Jasmin; Robrecht, Sandra; Becker, Natalia; Zucknick, Manuela; Rouhi, Arefeh; Weigel, Anja; Claus, Rainer; Weichenhan, Dieter; Eichhorst, Barbara; et al.
Abstract : B cell receptor (BCR) signaling is a key for survival of chronic lymphocytic leukemia (CLL) cells, and BCR signaling inhibitors are clinically active. However, relapse and resistance to treatment require novel treatment options. To detect novel candidate therapeutic targets, we performed a genome‐wide DNA methylation screen with custom arrays and identified aberrant promoter DNA methylation in 2, 192 genes. The transcription factor NFATC1 that is a downstream effector of BCR signaling was among the top hypomethylated genes and was concomitantly transcriptionally upregulated in CLL. Intriguingly, NFATC1 promoter DNA hypomethylation levels were significantly variant in clinical trial cohorts from different disease progression stages and furthermore correlated with Binet disease staging and thymidine kinase levels, strongly suggesting a central role of NFATC1 in CLL development. Functionally, DNA hypomethylation at NFATC1 promoter inversely correlated with RNA levels of NFATC1 and dysregulation correlated with expression of target genes BCL‐2, CCND1 and CCR7 . The inhibition of the NFAT regulator calcineurin with tacrolimus and cyclosporin A and the BCR signaling inhibitor ibrutinib significantly reduced NFAT activity in leukemic cell lines, and NFAT inhibition resulted in increased apoptosis of primary CLL cells. In summary, our results indicate that the aberrant activation of NFATC1 by DNA hypomethylation and BCR signaling plays a major role in the pathomechanism of CLL. Abstract : What's new? Genetic defects underlying chronic lymphocytic leukemia (CLL) are frequently accompanied by epigenetic aberrations, particularly changes in DNA methylation. Here, hypomethylation in the promoter region of the transcription factor gene NFATC1 was identified in CLL patients and found to correlate with disease stage. NFATC1 hypomethylation was significantly greater in patients with high Binet disease stage compared to low‐stage disease, indicating a possible role for NFATC1 activity in CLL progression. The data further show that ibrutinib, an inhibitor of B cell receptor signaling, for which NFATC1 serves as a downstream effector, successfully blocked NFAT activity, resulting in CLL cell apoptosis.